Strengthening Self-Efficacy in Personal Hygiene Among Children of Indonesian Migrant Workers in Malaysia - Nofi Susanti; Aulia Annisa; Putra Apriadi Siregar; Prima Yanti Siregar; Apriliani Apriliani; Rani Suraya; Muhammad Rezebri; Hafsah Hafsah (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2025)
Children of migrant workers often face limited access to basic services and health education, which can negatively affect their personal hygiene practices. This community engagement initiative aimed to enhance self-efficacy and improve hygiene knowledge and behaviors among migrant children through simple, enjoyable, and contextually relevant approaches. The program was implemented at Sanggar Belajar Negeri Sembilan, Malaysia, in July 2025, involving a total sample of 30 children aged 7-13 years. The intervention combined interactive lectures, demonstrations of the seven-step of proper handwashing, or what is commonly known as CTPS or Cuci Tangan Pakai Sabun, and toothbrushing techniques, as through a modified educational board game based on Snakes and Ladders. Monitoring was conducted descriptively through baseline and final observations, along with informal oral questioning (without formal questionnaires) to assess changes in knowledge, attitudes, participation, and signs of self-efficacy. The results indicated meaningful practical improvements: over 80% of participants could identify 3-5 correct hygiene practices; children showed increased confidence in demonstrating the seven CTPS steps and expressed commitment to brushing their teeth at least twice daily; and high levels of active participation were observed (≥25 children engaged in discussions, Q&A, and games until the end of the session). The program was well received by both participants and facilitators, suggesting that a combination of brief lectures, simulation, and gamification is practically effective for promoting hygiene in migrant community contexts Keywords: Personal Hygiene, Migrant Children, Indonesia, Self-Efficacy, Malaysia